Book review - Childhood in Crossroads: Cognition and society in South Africa (1989): by Pamela Reynolds - Craig, Anita P.; Witz, Lauren D. (PINS-Psychology in Society, 2025)
Protest literature and post-Apartheid society There is, supposedly, a Chinese curse in which "to live in interesting times" is wished upon the victim. The interesting times in which many, if not most, black children in South Africa have lived since about 1976 could certainly be made into the stuff of curses - or books about growing up in a society in crisis. One such book is Childhood in Crossroads: Cognition and society in South Africa (1989). The author, Reynolds, writes in the introduction to her book, "...two themes that run through the study (are): the relationship between individual and society, and change as a continuous individual and social occurrence. A third theme describes and analyses situation and context specific to the nature of cognitive processes" (p.3). This focus is not only of interest to those working in the theoretical domain demarcated by Vygotsky (1978), but also promises to throw some light on the lives of children caught in the eye of the South African socio-political storm. Reynolds characterises the book as "the result of an ethnographic study of 7-year-old children in a South African squatter settlement" (p.1).